The Comparison between the Politeness Strategy in the Command Directive Speech Acts and Request in the Email Japanese Business - Syahadatina, Afrilia Wahyu; Roni, Roni; Ridwan, Phil Agus (International Journal for Educational and Vocational Studies, 2020)
The aimed of this study is to describe the functions and politeness strategies of command directive and requesting speech acts in Japanese business emails. In line with the objectives of the study, the method used was descriptive qualitative. The data source in this study is Japanese business email in the field of education. Then, the data were collected by referring to the note taking technique, the replace technique, and the determining element. The data analysis technique uses descriptive qualitative methods. The results showed that speakers use more politeness strategies to express the intention of command than request. In addition, it also found differences from the directive speech act for requesting and the directive speech act for commanding i.e. on the choice of the interlocutor to do or not do the speaker's wishes. In directive speech acts for request, the interlocutor to have more choices not to do what the speaker wants. Whereas the directive speech acts for command, the opponents feel burdened and have little choice not to do what the speaker wants